A dança negra de Ismael Ivo: a antropofagia de si como recurso para fazer dança como arte - Ferreira, Juliana de Oliveira (2021)
This paper dedicates itself to explore the performance of the brazilian black artist, choreographer and dancer, Ismael Ivo (1955). Born and raised in the Zona Leste, in the city of São Paulo, Ismael Ivo has an international dance career, recognized by his artwork and dance management. What makes his practice so unique, and what makes us interested in this study, is the construction of his work as an artist, presenting a black dance perspective that kept an enduring dialogue with the european and north-american cultures dance canons historically called art, and titling himself as “a good son of the anthropophagy”. Using this as a starting point, we intend to comprehend which are the aspects of a black art the does not isolate itself in imaginaries claiming of supposed “essentialized origins” by the tradition’s bias but a black art dedicated to “devour” different perspectives in the frequent construction of his poetic, presenting another way of existence of the black diaspora shaped as dance. Thereto, this analysis will use narratives over his life, images and some of his scenic spectacles, to comprehend as Ismael Ivo invented his understanding about anthropophagy as a resource to make himself exist as a black artist in the artistic dance area.